Psychiatric comorbidities in children with specific learning disability - (:unkn) unknown (CUMHURIYET UNIV TIP FAK PSIKIYATRI ANABILIM DALI, 2018)
Objective: Spesific learning disability (SLD) is a significant reason of academic failures during school age. Learning difficulties are frequent issues in childhood and adolescence that can potentially impair the personal, social and familial functionality of the child or the adolescent leading to psychiatric disorders. The aim of this research is to reveal the concomitant diagnoses of SLD cases. Methods: Our research was cross-sectional. Case group, clinical comparison group and healthy comparison group were composed of 66, 30 and 55 children, respectively. Sociodemographic Data Form, Schedule for Affective Disorders and Schizophrenia for School Aged Children-Present and Lifetime Version (SADS-PL), the Bender Visual Motor Gestalt Test and SLD diagnosis battery were used. The data were evaluated by using Pearson's chi square test, Fisher-Freeman-Halton test, Fisher's exact test and Yates' continuity correction test. Results: The mean ages of 14 girls (21.2%) and 52 boys (78.2%) that attended to our study were 9.18 and 8.91 respectively. It was found that 72.7% had a concomitant diagnosis and 27.3% had no other psychiatric diagnosis. The most frequent concomitant diagnoses of SLD were attention deficit hyperactivity disorder (ADHD), oppositional defiant disorder, separation anxiety disorder, social anxiety disorder, enuresis, and depression, respectively. Discussion: Our results were consistent with the literature reporting that dual comorbidity rate in children with SLD was high. It is known that the difficulty in school affects many areas such as peer relations, family relations, self-confidence and mental state. For this reason, the screening of psychiatric comorbidities and their interventions are the most important steps.
Keywords: dyslexia; attention deficit hyperactivity disorder; comorbidity; READING-DISABILITY; DISORDERS; ADOLESCENTS; DEPRESSION; DYSLEXIA; DIFFICULTIES; RISK; IMPAIRMENT; ATTENTION; STUDENTS